IMPACT OF COVID-19 HEALTH CARE EMERGENCY ON TRAUMA RELATED OUTCOMES - Mustafa, Fatima; Khan, Mumtaz Ahmed; Mustafa, Abdullah; Khan, Khushal; Hassan, Muhammad (Journal of Rawalpindi Medical College, 2023)
Objective: To determine the impact of Covid-19 healthcare emergency on trauma-related outcomes. Study Design: Cross-sectional observational study Duration and Place of Study: Emergency department of surgery and allied of –removed for blind review—-and from 1st March 2021 to 30th May 2021 for three months. Patients and Methods: A comparison was made between the number of trauma patients admitted to the emergency department during the pandemic and the patients admitted during the same period of the previous year in the same center (data extracted from hospital records). Furthermore, we compared trauma-related disorders, patterns of injuries, and clinical characteristics of trauma patients in our hospital during a pandemic with those in a non-pandemic. Results: The number of trauma patients in the pandemic was significantly lower than it was before Covid. Before Covid, 1520 (64.5%) were admitted to the emergency room (non-Covid group), whereas only 835 (35.5%) were admitted to the emergency room during the pandemic (Covid group). There was a 48 % reduction in total. Gender and age ratios did not differ much between the two groups. Between cohorts, there was a significant association between mechanism of injury and type of trauma (p<0.03). Mortality rates decreased during the Covid-19 era (1.3% vs. 3.4%). Conclusion: As a result of the Covid-19 outbreak, there was a 48% decrease in trauma patients admitted to hospitals and a decrease in their mortality as well. The findings of this study may open the new door to new ways of managing surgical emergencies without engulfing the already busy hospitals.